Gambaran dan Kajian Penerapan Standar Pelayanan Kefarmasian Di Puskesmas Kota Denpasar Berdasarkan Permenkes Nomor 74 Tahun 2016 - Dewi, I Gusti Ayu Agung Kristina; Parthasutema, Ida Ayu Manik; Putri, Dhiancinantyan Windydaca Brata (Bali International University, 2020)
Background: Puskesmas in Denpasar City do not have pharmacists to carry out pharmacy services as a whole according to the standards, but only played by pharmaceutical technical personnel who can only carry out pharmaceutical services on a limited basis, according to Minister of Health Regulation Number 74 of 2016. Purpose: To describe the application of pharmaceutical service standards in Denpasar City health centers, as well as the factors that influence the implementation of pharmaceutical service standards at the health centers. Method: The study was conducted observationally with a descriptive research design, using questionnaires. The research subjects were those responsible for pharmacy in 11 Denpasar City health centers. Results: The application of pharmaceutical service standards in 11 Denpasar city health centers from the aspects of drug and medical management consumables reached 96.97%, from the aspect of clinical pharmacy services reached 63.85%, from aspects of pharmaceutical resources reached 73.58% and from aspects of service quality control reached 82.68%. Based on the results of the interview identified 18 factors that have the potential to mismatch the application of service standards. Conclusion: The standard of pharmacy services at the Denpasar City Health Center has not been carried out thoroughly according to the Permenkes No. 74 Tahun 2016.